Effect of solutions acidity on Haacke’s Figure of Merit of ZnO and ZnO:F thin films deposited by ultrasonic spray pyrolysis - Bobadilla-Barrón, G.; Maldonado, A.; Olvera, M. de la L.; Zamora-Justo, J. A. (Frontiers in Nanotechnology, 2024)
In this work, the deposition of highly conductive and transparent fluorine-doped ZnO thin films, deposited by chemical spray on glass substrates is reported. The effect of acetic (AcAc) in the initial fresh solution on Haacke's Figure of Merit (Φ) of both zinc oxide (ZnO) and fluorine-doped zinc oxide (ZnO:F) thin films was studied. The substrate temperature was fixed to 450 °C, and two deposition times (8 and 14 minutes) were tested. Accordingly, the optical and transport properties, as well as the structural and morphological characteristics of the films were measured. The results indicate that the samples are polycrystalline in all cases and exhibit a wurtzite-type structure of ZnO. The variation of AcAc in the starting solution causes a switch in preferential growth from (002) to (001). As the AcAc content increases, the surface morphology of the films reveals the formation of well-defined hexagonal grains, and the grain size increases. Conversely, the transmittance decreases as the acetic acid increases, which can attributed to carbon incorporation into the film. In addition, the band gap values of the films varied from 3.2 to 3.4 eV. Also, as the acetic acid concentration increased, a drop in the electrical resistivity of ZnO thin films on the order of 0.016 Ω•cm was found for the ZnO:F films deposited with fresh solution for 14 minutes. This can be ascribed to a dense acetic cloud formed during the synthesis process, trapping volatile F species that incorporate into the ZnO lattice. This enhances Haacke´s Figure of Merit of ZnO:F films deposited with a fresh solution, demonstrating their potential use for application as transparent conductive films. This contrasts with other synthesis methods that require longer aging time in the precursor solution, making these findings useful for large-scale and more efficient production of transparent conductive films.